Effects of self-monitoring and self-questioning strategies on comprehension of expository texts among students with learning disabilities in Ibadan (2016)
The study determined the effect of self-monitoring and self-questioning strategies on comprehension of expository texts among students with learning disabilities in Ibadan. Oyo State, Nigeria, using a pretest- posttest, control group, quasi-experimental research design with a 3 X 2 factorial matrix. Using a multi-stage sampling procedure, three secondary schools and sixty (60) students with learning disabilities were selected and assigned to two experimental groups (self- monitoring and self-questioning) and control group. The Pupil Rating Scale (r = 0.89), Expository Text Difficulty Test (r = 0.91), Reading Comprehension Test on Civic Education Expository Passages (r = 0.79) and Modified Sherer Self-efficacy scale (r = 0.82) were the instruments used for the study. Participants in the experimental group* were instruct tonally guided while those in the control group were taught with the conventional method. Three hypotheses were tested at 0.05 significant level, and data analysed, using Analysis of Covariance (ANVOCA), estimated marginal mean and Sidak post hoc test. The main effect of treatment was found to be significant (F(2.57) = 20.217; p< 0.05; η(2)= .822). In effect, participants exposed to self-monitoring strategy had the highest mean score of (x = 16.20), followed by those in self- questioning strategy group (x = 15.60), showing better performance than the control group (x = 10.30). The result also revealed that the main effect of self-efficacy is significant on comprehension of expository texts among students with learning disabilities (F(1.58) = 48.720 p <0.05,η(2) = .457). Also, the interaction effect of treatment and self-efficacy was significant (F(2.57) = 16.394; p< 0.05; η(2) = .822). This implies that self-efficacy equally played a significant role in enhancing performance of the students in expository texts. Based on these findings; useful recommendations were made: which included that teachers of students with learning disabilities should adopt self-monitoring and self-questioning strategies to teach comprehension of expository texts to students with learning disabilities.